Art of the loom : 32 tapestries woven on the loops of Mark Deweer's factory, Otegem, Belgium - Deweer Gallery, Otegem (Otegem : Deweer art gallery, 2010)
Stephan Balkenhol, Sergey Bratkov, Tony Cragg, Jan De Cock, Stefaan Dheedene, Jan Fabre, Günther Förg, Ilya Kabakov, Thomas Lange, Matthieu Laurette, Josef Felix Müller, Panamarenko, Anne-Mie Van Kerckhoven, Koen Vanmechelen
Tentoonstelling: Berlijn: 6 October - 14 November 2010, enz.
boek